2016
DOI: 10.3390/ijms17101673
|View full text |Cite
|
Sign up to set email alerts
|

Plant Resistance Inducers against Pathogens in Solanaceae Species—From Molecular Mechanisms to Field Application

Abstract: This review provides a current summary of plant resistance inducers (PRIs) that have been successfully used in the Solanaceae plant family to protect against pathogens by activating the plant’s own defence. Solanaceous species include many important crops such as potato and tomato. We also present findings regarding the molecular processes after application of PRIs, even if the number of such studies still remains limited in this plant family. In general, there is a lack of patterns regarding the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 163 publications
(212 reference statements)
1
44
0
4
Order By: Relevance
“…The fermentation liquid used in this study was derived from water extract of over-fermented tempe that reported to contain a non-proteinogenic amino acid, aminobutyric acid (Koh et al, 2012). β-aminobutyric acid (BABA), one of monomer of aminobutyric acid is known to have wide-ranging protection in a number of plant families against a variety of plant pathogens, nematodes and insect herbivores (Alexandersson et al, 2016). BABA has been demonstrated to reduce the performance of the pea aphid, Acyrthosiphon pisum on six legume plant species when applied as a root drench (Hodge et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation liquid used in this study was derived from water extract of over-fermented tempe that reported to contain a non-proteinogenic amino acid, aminobutyric acid (Koh et al, 2012). β-aminobutyric acid (BABA), one of monomer of aminobutyric acid is known to have wide-ranging protection in a number of plant families against a variety of plant pathogens, nematodes and insect herbivores (Alexandersson et al, 2016). BABA has been demonstrated to reduce the performance of the pea aphid, Acyrthosiphon pisum on six legume plant species when applied as a root drench (Hodge et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their structural similarity, phosphites are thought to be akin to phosphates. However, the use of phosphites as fungicides and biostimulants to control plant pathogens is widely accepted, but their use as a phosphorus source in plant nutrition is currently debated (Borza et al, 2014;Gómez-Merino and Trejo-Téllez, 2015;Alexandersson et al, 2016;Manna et al, 2016). Such difference gives .…”
Section: Fully Bilingual Revista Mexicana De Fitopatologíamentioning
confidence: 99%
“…La sustitución del oxígeno da lugar a profundas diferencias en la manera en que los fosfatos y fosfitos se comportan en los organismos vivos (McDonald et al, 2001;Achary et al, 2017). Debido a su similitud estructural, los fosfitos son considerados como análogos de los fosfatos, sin embargo, el uso de los fosfitos como fungicidas y bioestimulantes para el control de patógenos de plantas es ampliamente aceptado, pero su utilización como fuente de fós-foro en la nutrición de plantas es actualmente debatida (Borza et al, 2014;Gómez-Merino y TrejoTéllez, 2015;Alexandersson et al, 2016;Manna et al, 2016). Además, esa diferencia da a los fosfitos una mayor movilidad en el suelo y en los tejidos de las plantas, así como una mayor capacidad para penetrar a través de hojas, tallos y raíces (Tkaczyk et al, 2016).…”
Section: Fully Bilingual Revista Mexicana De Fitopatologíaunclassified
See 2 more Smart Citations